Entrepreneurship Learning as a Driver of Entrepreneurial Interest among Senior High School Students - Serli Razak; Muhammad Yany; Emmi Azis (Yayasan Ahmar Cendekia Indonesia, 2026)
students at a public senior high school in Bone Regency, Indonesia. The study was motivated by the observation that classroom instruction in entrepreneurship has remained largely theoretical, with limited opportunity for direct practice, which is presumed to constrain students' interest in starting a business. A quantitative ex post facto design was employed. Data were collected through a five-point Likert-scale questionnaire distributed to 40 students selected by simple random sampling from a population of 159 eleventh-grade social science students, and were analysed using simple linear regression with the assistance of SPSS version 26. Prior to hypothesis testing, the instrument was confirmed to be valid and reliable, and the classical assumption tests indicated that the data were normally distributed, linearly related, and free from heteroscedasticity. The results show that entrepreneurship learning exerts a positive and significant influence on students' entrepreneurial interest, as reflected in the regression equation Y = 2.004 + 1.026X and a calculated t-value that substantially exceeds the critical t-value at the 0.05 level. The coefficient of determination indicates that entrepreneurship learning accounts for the great majority of the variance in entrepreneurial interest, while the remaining variance is attributable to factors outside the scope of this study. These findings suggest that strengthening the quality of entrepreneurship instruction, particularly through more practice-based and contextual approaches, is an effective strategy for cultivating entrepreneurial interest among senior high school students.